Effects of dispersal strategy and migration history on genetic diversity and population structure of Antarctic lichens - Lagostina, Elisa; Andreev, Mikhail; Dal Grande, Francesco; Grewe, Felix; Lorenz, Aline; Lumbsch, H. Thorsten; Rozzi Marin, Ricardo Roberto; Ruprecht, Ulrike; Garcia Sancho, Leopoldo; Sochting, Ulrik; Scur, Mayara; Wirtz, Nora; et al. (My University, 2021)
Aim The homogenisation of historically isolated gene pools has been recognised as one of the most serious conservation problems in the Antarctic. Lichens are the dominant components of terrestrial biotas in the Antarctic and in high mountain ranges of southern South America. We study the effects of dispersal strategy and migration history on their genetic structure to better understand the importance of these processes and their interplay in shaping population structure as well as their relevance for conservation. Location Maritime Antarctic and southern South America. Methods Populations of three fruticose lichen species, Usnea aurantiacoatra, U. antarctica and Cetraria aculeata, were collected in different localities in the Maritime Antarctic and southern South America. Usnea aurantiacoatra reproduces sexually by ascospores, whereas the other two species mostly disperse asexually by symbiotic diaspores. Samples were genotyped at 8-22 microsatellite loci. Different diversity and variance metrics, Bayesian cluster analyses and Discriminant Analysis of Principal Components (DAPC) were used to study population genetic structure. Historical migration patterns between southern South America and the Antarctic were investigated for U. aurantiacoatra and C. aculeata by approximate Bayesian computation (ABC). Results The two vegetative species display lower levels of genetic diversity than U. aurantiacoatra. Antarctic populations of C. aculeata and South American populations of U. aurantiacoatra display much stronger genetic differentiation than their respective counterparts on the opposite side of the Drake Passage. Usnea antarctica was not found in South America but shows comparably low levels of genetic differentiation in Antarctica as those revealed for U. aurantiacoatra. Phylogeographic histories of lichens in the region differ strongly with recent colonisation in some instances and potential in situ persistence during Last Glacial Maximum (LGM) in others. Patterns of genetic diversity indicate the presence of glacial refugia near Navarino Island (South America) and in the South Shetland Islands. ABC analyses suggest that C. aculeata colonised the Antarctic from Patagonia after the LGM. Results for U. aurantiacoatra are ambiguous, indicating a more complex population history than expressed in the simplified scenarios. Main Conclusions Mode of propagation affects levels of genetic diversity, but the location of glacial refugia and postglacial colonisation better explains the diversity patterns displayed by each species. We found evidence for glacial in situ survival of U. aurantiacoatra on both sides of the Drake Passage and postglacial colonisation of Antarctica from South America by C. aculeata. Maintaining the strong genetic differentiation of Antarctic populations of C. aculeata requires strict conservation measures, whereas populations of U. aurantiacoatra are exposed to a much lower risk due to their higher diversity and connectivity.
Keywords: approximate bayesian computation; biodiversity; cetraria aculeata; climate change; conservation; microsatellites; parmeliaceae; u; aurantiacoatra; usnea antarctica